Human-Elephant Taskforce products available for research collaborators - Richard Hoare (Pachyderm)
This text notes that a number of products emanating from the ongoing work of the Human-Elephant Conflict Taskforce are available with the hope that people will use them and comment on the results. The plan is to establish a standardized approach with a feedback loop so the research results are comparable between vastly differing human-elephant conflict (HEC) sites in Africa. The product list thus far includes: a HEC bibliographic list; a recommended standardized data collection and analysis protocol for HEC situations; a training package for enumerators of elephant damage; and a synthesis of recent research into aspects of human-elephant conflict in Africa as represented in a set of reports from eight studies undertaken in 1998-1999. Notes that maps of HEC sites, a decision support sytem for HEC management and GIS capability through the AED are under development.